2020
DOI: 10.1097/nna.0000000000000881
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Work Environment and Patient Outcomes in a Hospital Context

Abstract: OBJECTIVE The aims of this study were to summarize the current state of knowledge regarding the relationship between nursing work environment (NWE) and patient outcomes and to identify gaps in the literature. BACKGROUND There was an increased awareness of the impact of NWE on patient outcomes, in particular, related to safety and quality of care. METHOD Scoping review was conducted. Studies published between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
4
10
0
Order By: Relevance
“…To address the gap in research, we examined individual, evidence, and contextual factors associated with implementation of EBMPs by nurse managers. We studied five EBMPs for improving NWEs because of the robust research linking better NWE and patient outcomes (Nascimento & Jesus, 2020) and nurse managers’ instrumental role in managing both NWE and nurse‐sensitive patient outcomes. We found that each of the five EBMPs studied had a unique profile of predictors associated with its implementation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To address the gap in research, we examined individual, evidence, and contextual factors associated with implementation of EBMPs by nurse managers. We studied five EBMPs for improving NWEs because of the robust research linking better NWE and patient outcomes (Nascimento & Jesus, 2020) and nurse managers’ instrumental role in managing both NWE and nurse‐sensitive patient outcomes. We found that each of the five EBMPs studied had a unique profile of predictors associated with its implementation.…”
Section: Discussionmentioning
confidence: 99%
“…To address the identified knowledge gap, the primary purpose of this study was to examine individual, evidence, and contextual factors associated with nurse manager‐reported implementation of EBMPs for improving NWEs across 10 public health system hospitals in New York City (NYC) using the Integrated Promoting Action on Research Implementation in Health Services (PARIHS) implementation science framework (Harvey & Kitson, 2016). The study results can inform the development of effective organizational and policy interventions to support nurse managers in implementing EBMPs to improve NWEs and, consequently, patient outcomes associated with better NWEs (Nascimento & Jesus, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of researchers worldwide have been studying the relationship between the perception of the nursing practice environment and patients, nursing professionals and institution outcomes (Aiken et al, 2018; Balsanelli & Cunha, 2013; Gasparino et al, 2019; Nascimento & Jesus, 2020).…”
Section: Introductionmentioning
confidence: 99%